PLOT AND COMPOSITION FEATURES, CHARACTERS, AND ISSUES IN IVAN TURGENEV’S A SPORTSMAN’S SKETCHES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the plot and composition features, characters, and thematic issues in Ivan Turgenev’s A Sportsman’s Sketches. The cycle of sketches is examined as a cohesive literary work that combines lyrical descriptions of Russian nature with sharp social critique, particularly concerning the lives of peasants under serfdom. The article investigates the structure of the collection, the recurring motifs and narrative techniques employed by Turgenev, as well as the main character archetypes. Special attention is given to the moral and philosophical problems presented in the sketches, including questions of human dignity, social injustice, and the role of the nobility in Russian society. By analyzing A Sportsman’s Sketches from both literary and historical perspectives, the article aims to reveal its enduring relevance and contribution to the development of Russian realism and its influence on public opinion in the 19th century.